Tuning of the Optical Properties in Photonic Crystals Made of Macroporous Silicon. (29th May 2008) - Kitzerow, Heinz-S.; Matthias, Heinrich; Schweizer, Stefan L.; van Driel, Henry M.; Wehrspohn, Ralf B.
Abstract : It is well known that robust and reliable photonic crystal structures can be manufactured with very high precision by electrochemical etching of silicon wafers, which results in two- and three-dimensional photonic crystals made of macroporous silicon. However, tuning of the photonic properties is necessary in order to apply these promising structures in integrated optical devices. For this purpose, different effects have been studied, such as the infiltration with addressable dielectric liquids (liquid crystals), the utilization of Kerr-like nonlinearities of the silicon, or free-charge carrier injection by means of linear (one-photon) and nonlinear (two-photon) absorptions. The present article provides a review, critical discussion, and perspectives about state-of-the-art tuning capabilities.